2014
DOI: 10.1097/yic.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of functional improvement in employed adults with major depressive disorder treated with desvenlafaxine

Abstract: We carried out a secondary analysis of a double-blind, placebo-controlled trial of desvenlafaxine for major depressive disorder (MDD) to explore the associations between depressive symptoms and subtypes, and functional outcomes, including work functioning. Employed outpatients with MDD were assigned randomly in a 2 : 1 ratio to receive desvenlafaxine 50 mg/day or placebo for 12 weeks. Analyses were carried out post-hoc with the intent-to-treat (ITT) sample (N=427) and a prospectively defined modified ITT sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
5
12
0
Order By: Relevance
“…Our findings of improvement in activity impairment with treatment are consistent with those previously reported by Lam et al22 The strength of correlation between levels of depression severity and activity impairment in our report (correlation coefficient =0.54 and 0.57 during acute and continuation phases, respectively) are also comparable to those reported by Lam et al22 (correlation coefficient between activity impairment and HRSD17 =0.56). Previous studies have reported that depressed patients place greater importance to improvement in functioning as compared to reduction in depression severity 44,45.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings of improvement in activity impairment with treatment are consistent with those previously reported by Lam et al22 The strength of correlation between levels of depression severity and activity impairment in our report (correlation coefficient =0.54 and 0.57 during acute and continuation phases, respectively) are also comparable to those reported by Lam et al22 (correlation coefficient between activity impairment and HRSD17 =0.56). Previous studies have reported that depressed patients place greater importance to improvement in functioning as compared to reduction in depression severity 44,45.…”
Section: Discussionsupporting
confidence: 93%
“…Antidepressant treatment results in reduced activity impairment 22. However, the clinical significance of these improvements is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has established efficacy over placebo at the approved doses of 50 mg/d and 100 mg/d in multiple clinical trials, and its efficacy has been demonstrated across age and sex subgroups and in patients with metabolic syndrome or anxious or severe depression at baseline in pooled post hoc analyses . Treatment with desvenlafaxine has also been shown to improve functional outcomes and quality‐of‐life measures compared with placebo in clinical trial patients …”
mentioning
confidence: 99%